Modifikasi Model Formulasi Kebijakan Perencanaan Pembangunan Perdesaan Berbasis Partisipasi Publik - Ahmad Sururi (Program Studi Administrasi Negara Universitas Serang Raya, 2017)
The purpose of this study was to analyze how the typology of policy formulation solutions in solving public problems and how to model public policy formulation of development planning based on public participation. Research method in this research use qualitative method. This research was conducted in Wanasalam District, Lebak Regency, exactly in Cilangkap Village. Data collection techniques through interviews, observation, documentation and review of documents from various sources and references. Data analysis techniques performed through data reduction, data presentation and data verification. The results and discussion in this research there are 5 (five) solution typology in solving public problem that is: 1)Inducment, policy step that is persuading or pressing over certain issue; 2)Rules, policy measures that emphasize the establishment of rules in the form of regulations that must be adhered to by the community; 3)Facts, policy steps in the form of use of information paths to persuade target groups to want to do something that is considered to solve the problem; 4)Right, policy measures in the form of giving rights or duties to the community; 5)Power. policy efforts in the form of additional weight of power caused by certain demands. Then, the process of modifying the formulation of a public-based rural development planning policy requires synergy between the village government and the community through policy recommendations to the formal policy actors in development planning forums and citizens' debates. The synergy of the three components within the framework of modification of the policy formulation is a continuous process called input (consisting of public choices), the policy process (through Musrenbang and Rembug rakyat forums) and output/outcome (policy formulation of public participation based development planning).